Solar thermal electric power systems: final report, volume I, executive summary - Colorado State University. Solar Energy Applications Laboratory, author; Westinghouse Electric Corporation, author; Colorado State University. Solar Energy Applications Laboratory, author; Colorado State University. Department of Civil Engineering, author; National Science Foundation, publisher (Colorado State University. Libraries, 1974)
The final report consists of three volumes: (1) an Executive Summary, (2) System Studies and Economic Evaluations, and (3) Appendices. The objective of the research program is to develop design parameters of systems for thermal/mechanical conversion of solar energy to electric power at minimum cost per kilowatt-hour generated. Systems of 3MW to 300MW sizes in a public utility network are considered. Parametric performance and cost models are derived for key elements of the system. A sequential optimization program was developed using these models to determine optimum subsystem sets and combinations which yield the least capital cost plants. A dynamic simulation program was developed to determine annual electric power produced by solar power systems at specific locations. Electric energy cost comparisons are made to select promising systems for generation of electricity from solar energy.
CER74-75SK14.
November 1974.
Prepared for the National Science Foundation Research Applied to National Needs, Washington, D.C.
NSF/RANN/SE/GI-37815/FR/74/3.
Keywords: Solar energy; Electric power-plants